Risk factors and natural history of parastomal hernia after radical cystectomy and ileal conduit. (6th December 2021) - Ghoreifi, Alireza; Allgood, Evan; Whang, Gilbert; Douglawi, Antoin; Yu, Wenhao; Cai, Jie; Miranda, Gus; Aron, Monish; Schuckman, Anne; Desai, Mihir; Gill, Inderbir; Daneshmand, Siamak; et al.
Abstract : Objective: To investigate the incidence, risk factors and natural history of parastomal hernia (PSH). Materials and Methods: We reviewed the records of patients who underwent radical cystectomy (RC) and ileal conduit (IC) procedure between 2007 and 2020. Patients who had available follow‐up computed tomography (CT) imaging were included in this study. All CT scans were re‐reviewed for detection of PSH according to Moreno‐Matias classification. Patients who developed hernia were followed up and classified into stable or progressive (defined as radiological upgrading and/or need for surgical intervention) groups. Multivariable Cox regression was performed to identify independent predictors of hernia development and progression. Results: A total of 361 patients were included in this study. The incidence of radiological PSH was 30%, graded as I (56.5%), II (12%) and III (31.5%). The median (interquartile range [IQR]) time to radiological hernia was 8 (5–15) months. During the median (IQR) follow‐up of 27 (13–47) months in 108 patients with a hernia, 26% patients progressed. The median (IQR) time to progression was 12 (6–21) months. On multivariable analysis, female gender (hazard ratio [HR] 1.86), diabetes (HR 1.81), chronic obstructive pulmonary disease (COPD; HR 1.78) and higher body mass index (BMI; HR 1.07 for each unit) were independent predictors for radiological PSH development. No significant factor was found to be associated with hernia progression. Conclusion: Radiological PSH after RC and IC occurred in 30% of patients, a quarter of whom progressed in a median time of 12 months. Female gender, diabetes, COPD and high BMI were independent predictors for radiological hernia development.